Control System Based on Fuzzy Logic In Nutmeg Oil Distillation Process - Syamsul Syamsul; Rudi Syahputra; Suherman Suherman; Zamzami Zamzami (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
The focus of this research is the application of electronic control on the distillation boiler of nutmeg oil. The control system is based on fuzzy logic and as the input parameter is temperature and vapor pressure. The temperature parameters are set in the range 80-120ºC, and the vapor pressure parameters are set in the range of 1-2.5 atmospheres. The output parameter is the time required in the distillation process. The optimal values of these input and output parameters are embedded in microcontroller based control. The control responds to the temperature and vapor pressure to select the gas flow rate at the distillation boiler. This experiment was conducted on a distillation system with a capacity of 25 kg of crushed dried nutmeg, manually and with control based on fuzzy logic. Conventional testing requires 6.90 kg of gas and applying fuzzy logic based control requires 5.50 kg of gas. The yield of nutmeg oil from the distillation process is 2.5 kg conventionally and 2.63 kg with fuzzy logic control. Based on the optimal time of 16 hours distillation process, there was a decrease of gas consumption by 20.3%.